Challenges in implementing emergency obstetric care (EmOC) policies: perspectives and behaviors of frontline health workers in Uganda - Mukuru, Moses; Kiwanuka, Suzanne N.; Gibson, Linda; Ssengooba, Freddie (Health Policy and Planning, 2021)
Uganda is among the sub-Saharan African Countries which continue to experience high preventable maternal mortality due to obstetric emergencies. Several Emergency Obstetric Care (EmOC) policies rolled out have never achieved their intended targets to date. To explore why upstream policy expectations were not achieved at the frontline during the MDG period, we examined the implementation of EmOC policies in Uganda by; exploring the barriers frontline implementers of EmOC policies faced, their coping behaviours and the consequences for maternal health. We conducted a retrospective exploratory qualitative study between March and June 2019 in Luwero, Iganga and Masindi districts selected based on differences in maternal mortality. Data were collected using 8 in-depth interviews with doctors and 17 midwives who provided EmOC services in Uganda’s public health facilities during the MDG period. We reviewed two national maternal health policy documents and interviewed two Ministry of Health Officials on referral by participants. Data analysis was guided by the theory of Street-Level Bureaucracy (SLB). Implementation of EmOC was affected by the incompatibility of policies with implementation systems. Street-level bureaucrats were expected to offer to their continuously increasing clients, sometimes presenting late, ideal EmOC services using an incomplete and unreliable package of inputs, supplies, inadequate workforce size and skills mix. To continue performing their duties and prevent services from total collapse, frontline implementers’ coping behaviours oftentimes involved improvization leading to delivery of incomplete and inconsistent EmOC service packages. This resulted in unresponsive EmOC services with mothers receiving inadequate interventions sometimes after major delays across different levels of care. We suggest that SLB theory can be enriched by reflecting on the consequences of the coping behaviours of street-level bureaucrats. Future reforms should align policies to implementation contexts and resources for optimal results.
Keywords: Emergency Obstetric Care; MDG 5; Implementation; Street-level bureaucrats; Uganda